Teachers’ Perception of the English Curriculum Change in Costa Rica: The Action-Oriented Approach - Vargas Solís, María Antonieta (2023)
This qualitative study explores the perception of eight seventh-grade teachers from academic schools in the western region of Costa Rica about implementing the action-oriented approach (AOA). As the main objective, the researchers sought to assess the professors' perception of the execution of this approach in order to explore its precision regarding its principles and the guidelines of the Ministerio de Educación Pública de Costa Rica. The data were collected through a semi-structured interview and then coded considering three primary constructs: the participants’ definition of AOA, its strengths and weaknesses, and the continuities, variations, and innovations that arose with the change from the CLT to the AOA. Regarding the coding, the researchers carried it out under the principles of grounded theory to identify commonalities among participants. The results show a favorable perception of the approach, yet the individuals could not clearly define the AOA for they perceived the materials, the student, and the teacher’s roles as strengths; and tests, materials, and planning as weaknesses. The continuities and variations were not tied to the approach and the most salient innovations were the teacher’s guide and the mini-project. The researchers concluded that there exist discrepancies between the participants’ understanding of the AOA and the actual tenets of the approach.